Scenes and Adventures in Spain: Spain during the First Carlist War: The Experience of a British Correspondent - Abradelo de Usera, Mª Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The present article is aimed at studying the travel book of one of the correspondents that the British Newspaper The Morning Chronicle sent to cover the First Carlist War. John Moore, Poco Mas, as many other contemporary journalists did, uses his notes taken in the battlefield and his reflections to publish, years later, his personal views on the conflict. He also reflects the characteristics of a country and a society which is different from his own. He describes its peculiar customs, and its reaction against a conflict that was diminishing its population, exhausting its resources, and destroying its valuable cultural heritage.